2016
DOI: 10.1038/srep24755
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1-like retrotransposons contribute to RNA-based gene duplication in dicots

Abstract: RNA-based duplicated genes or functional retrocopies (retrogenes) are known to drive phenotypic evolution. Retrogenes emerge via retroposition, which is mainly mediated by long interspersed nuclear element 1 (LINE-1 or L1) retrotransposons in mammals. By contrast, long terminal repeat (LTR) retrotransposons appear to be the major player in plants, although an L1-like mechanism has also been hypothesized to be involved in retroposition. We tested this hypothesis by searching for young retrocopies, as these stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Our previous work in plants has found that LTR-and non-LTR-mediated retroposition appear to occur with roughly equal rates in dicots (Arabidopsis thaliana and Manihot esculenta) (Zhu et al 2016). In this work, we confirm that L1-mediated retroposition is the dominant mechanism of retroposition in human and mouse (Kaessmann et al 2009).…”
Section: Org Downloaded Fromsupporting
confidence: 76%
“…Our previous work in plants has found that LTR-and non-LTR-mediated retroposition appear to occur with roughly equal rates in dicots (Arabidopsis thaliana and Manihot esculenta) (Zhu et al 2016). In this work, we confirm that L1-mediated retroposition is the dominant mechanism of retroposition in human and mouse (Kaessmann et al 2009).…”
Section: Org Downloaded Fromsupporting
confidence: 76%
“…This observation (Ohshima 2013) has prompted additional studies including a recent work in Arabidopsis thaliana and cassava (Zhu et al 2016), two dicots harboring both LINE and SINE sequences in their genome. Zhu and colleagues found that some retroCNVs maintain the footprints of reverse transcription and insertion mechanisms (see section “Evolutionary insights from retroCNVs”) and that a few young retrocopies were likely generated by LINE retroelements.…”
Section: Mechanisms Of Retrocopy Formationmentioning
confidence: 97%
“…Discoveries of LTR retroelement sequences flanking single genes in maize (Bureau et al 1994; Jin and Bennetzen 1994) have been followed by genome-wide investigations of LTR elements involved in retrogenes formation in rice (Wang et al 2006), Arabidopsis (Zhu et al 2016) and more recently of retroCNVs in animals (Tan et al 2016). It does seem that, as initially observed for the Ty1 element in yeast (fig.…”
Section: Mechanisms Of Retrocopy Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrocopies have been identified in the genomes of Drosophila melanogaster (Schrider et al 2011), nematode (Zou et al 2012), human (Ohshima et al 2003, Zhang et al 2003, Vinckenbosch et al 2006, mammals (Pan andZhang 2009, Carelli et al 2016) and fish (Fu et al 2010, Du andHe 2015). In plants, hundreds of retrocopies have been found in Arabidopsis (Zhang et al 2005, Benovoy and Drouin 2006, Zhu et al 2016, rice (Wang et al 2006, Sakai et al 2011, Populus (Zhu et al 2009) and green algae (Jakalski et al 2016) via genome-wide analysis. These studies provide further support for the importance of retroposition in genome evolution (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%